ANGULĪ PRAMĀNA, AN ANCIENT TOOL OF MEASUREMENT: A CRITICAL REVIEW - Visave Pratibha; Shukla Deepnarayan (International Journal of Applied Ayurved Research, 2019)
Ayurveda is one of the ancient sciences in India. Pramāna shārīr is one of the concepts stated in Ayurveda. It especially deals with the measurements of the human body. As there were no stand-ard units of measurement, our sages discovered the unique method of measurement i.e. Angulī pramāna. It has individualistic approach as individual’s own finger width is used to measure the body parts. Hence it is also known as swa-angulī pramāna. Measurements of different body parts is already given by our āchāryas thousands of years ago. All these measurements are in terms of angulī. Though these measurements are stated in Ayurveda in ancient period, they are valid in the recent era too. Anthropometry is the modern counterpart of the Pramāna Shārīr. Anthropom-etry is a branch of Anthropology that involves the quantitative measurements of human body. It is a single most portable, universally applicable, inexpensive and non-invasive technique for as-sessing the size, proportions and compositions of the human body. Pramāna shārīr remained untouched aspect in clinical practice due to its unexposed practical application. So as to get the excellence in clinical practice in Ayurveda, one must know the pramāna of the body as well.